FOOD COST CONTROL ANALYSIS BY COST CONTROLLER ON FAIRMONT SANUR BEACH BALI - I Gusti Ayu Putu Kartika Dewi; I Nyoman Winia; Ida Ayu Elistyawati; Kanah Kanah (Politeknik Negeri Bali, 2018)
This study is a case study, aimed at studying the method and process in use in determining food cost in the hotel industry. In addition, it also aimed at identifying the cause of percentage difference between the actual food cost and the raw materials food cost (standard food cost). The case study was done in Fairmont Sanur Beach Bali. The study employed two methods of data analysis: 1) Quantitatively method by calculating the percentage of standard food cost and actual food cost, and subsequently, compare the two costs. 2) Qualitative descriptive methods by providing reviews or interpretation of the data and information obtained with regards to the existing theories on inventory management: purchase procedure, receipt, storage, and raw material expenditure (Wiyasha, 2011; Dittmer and Keefe, 2009). The data is collected through observation. The results of this study show, firstly, food cost control at the Fairmont Sanur Beach Bali has not been done optimally. This is pointed out by the presences of difference between the actual and standard food cost. Based on the data, this situation results from the high levels of purchases and gross food consumption; and the absence of the implementation of third party’s food processing and presentation standard which also results in higher food cost. The second result of this study is the presence of inconsistent food standard. According to the data, this condition is caused by the selection of food suppliers which are exclusively based on the lowest price. Standards are Standard Purchase Specification, Standard Yield, Standard Recipe, and Standard Portion Size.